(3RgQ GdTeGQjN aj Yde GdJGQjNs - (3CHhRjO GdaGSj , YHO GdQMef Hf YHO GdbGOQ Hf Ydj Hf CHj GdeMGSf jhSa GdaGSj,J (B1096 (3g` s
(3ChdgG (B:s
(3hHYO aGdJGQjN Yde hGSY hGdGYJHGQ ajg efg fGaY hGdbhe de jCdhG ef GdJUfja ajg ef GdCfhGY hGdJUfja s
(3BNQgG (B:s
(3GdMeO ddg Jhdi GdNdGaI ehdGfG GdQTjO Hf ehdGi eMeO Hf ehdGi Ydi GdTQja GdMSfi s
(3efXheIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B310 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B145s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B695 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B221 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(56(3O(B) s
Keywords: (3GdJGQjNs